Pleomorphic adenoma of a deep orbital ectopic lacrimal gland. (2nd September 2016) - Misra, Somen; Bhandari, Akshay; Misra, Neeta; Gogri, Pratik; Mahajan, Shruti
ABSTRACT: Ectopic lacrimal gland, being one of the choristomas, is comprised of lacrimal gland tissue outside the lacrimal gland fossa in the fronto-lateral part of the orbital roof. Ectopic lacrimal gland is a rare condition where the gland may be found in the orbit, eyelids, ocular adnexa or within the globe. Neoplastic transformation of such tissue may occur. A sixty-two-year old male patient presented with right eye proptosis and slight nasal displacement of the globe. Computerized tomography scan revealed a well-defined hypodense lesion of size 19 x 18 x 20 mm supero-lateral to lateral rectus muscle, with mild proptosis and thinning of the right lateral orbital wall. Excisional biopsy was performed through a lateral orbitotomy approach. A well circumscribed globular mass was removed from the right orbit, well behind the fossa for the lacrimal gland in the retrobulbar space. Histopathology was suggestive of pleomorphic adenoma of lacrimal gland. Pleomorphic adenoma is an epithelial tumor of the lacrimal gland which is extremely rare from an ectopic lacrimal gland and only few cases have been reported in literature till date.